Ventilation via nose cone results in similar hemodynamic parameters and blood gas levels as endotracheal intubation during open chest surgery in rats. (April 2022) - Krutrök, Nina; Pehrsson, Susanne; Van Zuydam, Natalie; Jennbacken, Karin; Wikström, Johannes
Open chest surgery in rodents requires assisted breathing and the most common approach for ventilation is via an endotracheal tube. Even with well-trained operators the endotracheal intubation is technically challenging and may lead to prolonged procedures and endotracheal intubation complications. Nose cone ventilation is a simpler procedure compared to endotracheal intubation and has the potential to improve animal welfare by reducing procedure time and endotracheal intubation associated complications. Rats are obligate nose breathers, and therefore replacing intubation with air supply from a nose cone would be an advantage and a more natural way of breathing. Here, we compared the values for several blood gases, blood pressure and heart rate from rats that were nose cone ventilated with rats that underwent endotracheal intubation at 12 timepoints equally distributed across three surgical stages: baseline, open chest and closed chest. Throughout the monitoring period the hemodynamic and blood gas values for both methods of ventilation were within published, normal ranges for the rat and were biologically equivalent (equivalence test p value ≤ 0.05). Our data showed that nose cone ventilation-maintained blood gases and hemodynamic homeostasis equivalent to endotracheal intubation. Nose cone ventilation can be recommended as an alternative to endotracheal intubation in rat experiments where investigators require airway control.